Variation of fatness and energy content of the body with body condition score in sport horses and its prediction - Martin-Rosset, William; Vernet, H; Dubroeucq, H; Arnaud, G; Picard, A; Vermorel, M (MTT, 2008)
This study aimed at studying the variation of the weight of adipose tissue and muscles and their energy content in total body; validating a body condition score method (BCS) designed by INRA; and performing models for predicting the weight of adipose tissues and the net energy content (NEC) of the body reserves (e.g. all adipose tissues or/and muscles). Twenty adult horses of French sport breeds (Selle Français or Anglo-Arab) with average body weight of 501 kg and body condition score ranging between 1.0 and 4.5 according to INRA's method (scale 0 to 5), were slaughtered. The muscles and the different adipose tissues (subcutaneous, internal, and inter-muscular) were dissected and weighted. Energy content of all those tissues was determined in each horse using adiabatic calorimeter. The weight of the different adipose tissues (WAT) increased with BCS according to the general models: WAT (kg) = a exp BCS (0.986 < R² < 0.990, P < 0.001). Energy concentration (Ec) of those different adipose tissues rises with BCS according to the general models: Ec (kcal/g) = a + b Log BCS (0.975 < R² < 0.990, P < 0.001. Total energy content (TEC) of empty body weight (EBW) rises with BCS according to the general model EBWTEC (kcal) = a exp BCS (R² = 0.993, P < 0.001). Total energy content of EBW ranges from 297 to 1035 Mcal whereas EBW varies between 335 to 525 kg. All these models of prediction have been used to perform energy balance of exercising horses in the scope of feeding trials implemented to evaluate INRA 1990 requirements.
Keywords: Ko; horse; body composition; body score; energy